MANAJEMEN PENDIDIK DAN TENAGA KEPENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN - Nurlindah Nurlindah; Muh. Khalifah Mustami; Musdalifah Musdalifah (Idaarah: Jurnal Manajemen Pendidikan, 2020)
The purpose of this research is to reveal the activity of management realization and personel education and find an effort done to increase the quality education by education management and personel education. The kind of this research is descriptive qualitative research in Al-Mansur Biangloe boarding school Bantaeng regency. Data collection methods by interview, observation and documentation. The result of research show that the implementation educator management and personel education at palnning step, selection, orientation, appointment and placement, observation and assessment, giving compensation and discharge have been done but it is not still maximal, there are still educator and staf education not based on their expert, compensation given is not able to make prosperous for them. The things to do to increase the quality by good planning, and selecting of what the school need, developing by training, sertified, observation and compensation as a fair to defend educator.